Study on the compaction characteristics of snow on airport runways under vertical load - Hanqing Guo; Hao Zhang; Boyuan Ping; Juquan Yang; Yanyu Cui; Qingmiao Ding (PLoS ONE, 2025)
Snow accumulation on airport runways reduces friction, affecting aircraft takeoff and landing performance, as well as operational efficiency and safety. Previous studies have primarily focused on the bearing capacity and mechanical properties of compacted snow. However, there is limited research on the compaction characteristics of naturally loose snow under vertical loads. This study employs the Arbitrary Lagrangian-Eulerian (ALE) method to construct a snow model based on the Modified Drucker Prager Cap (MDPC) Model, analyzing the compaction characteristics of snow under aircraft tires with varying snow thicknesses (5 mm to 50 mm) and vertical loads (250N to 2250N). The results indicate that when the snow thickness is less than the tire tread depth, the impact of vertical load on snow compaction displacement is negligible, maintaining a displacement of 3–5 mm. Conversely, when the snow thickness exceeds the tread depth, the compaction displacement increases with load until reaching a stable state. The compaction rate initially increases and then decreases with different snow thicknesses; beyond the tread depth, the load significantly affects the maximum compaction rate, which reaches 504 mm/s. Additionally, the density changes in the tire-snow contact area are influenced by both snow thickness and vertical load. As thickness and load increase, the duration for which the sidewall density exceeds that of the center also extends, with vertical load having a minimal effect on density transition.